The Difference in Immunoglobulin M Anti-Phenolic Glycolipid-1 Antibody Levels in Leprosy Patient, Household Contacts, and Control - Ramona Dumasari Lubis (Journal of Global Pharma Technology, 2019)
Background: Leprosy is a disease caused by M. leprae infection, may affect the peripheral nervous system, skin and other tissues. Until recently, leprosy is still a health problem in Indonesia. Phenolic Glycolipid-1 (PGL-1) is a stable and unique component of M. leprae, and an antibody examination against this antigen may play a role in assisting early detection of subclinical stage leprosy (SSL) and treatment monitoring. Objective: This study aims to define the level of IgM anti-PGL-1 antibody in leprosy patients, household contacts and controls and their serology status  Methods: The examination of IgM anti-PGL-1 antibody was carried out on 52 leprosy patients, 95 people household contacts and 95 healthy controls. The data from subjects were then analyzed and tested using Kruskal-Wallis statistical test and a p-value <0.001 was obtained. Results: It was obtained that the levels of IgM anti-PGL-1 antibody significantly differed between leprosy, household contact and control groups (p<0.05). Most of the leprosy patients had seropositive status, contrary to dominant seronegative that was found in household contacts and control groups. In subgroup analysis, the IgM titer level did not significantly differ between household contacts and control groups (p=0.122). Conclusion: the IgM anti-PGL-1 antibody differed between leprosy and household contacts and control. IgM antibody titer may also depict a person's exposure status to M. leprae bacilli.Keywords: M. leprae, Leprosy, IGM anti-PGL-1 antibody, Household contacts.